2012
DOI: 10.1111/rda.12041
|View full text |Cite
|
Sign up to set email alerts
|

Results of GnRH Agonist Implants in Oestrous Induction and Oestrous Suppression in Bitches and Queens

Abstract: Contents Over the last 10–15 years, long‐acting GnRH agonists have become widely available. In the field of small animal reproduction, most recent studies have focused on the use of two compounds developed under the form of subcutaneous implants: azagly‐nafarelin and deslorelin. Only the latter has been commercially available for use in male dogs, first in Australia and New Zealand, then in several countries of the European Union since 2008. Although officially marketed for male dogs, this compound has also be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 17 publications
0
27
0
2
Order By: Relevance
“…The size of the litters was similar to that in our previous studies of Beagle breeding using the Ovulation Timing and Ovarian Assessment Test Kit. 15 It may be that deslorelin leads to a poor pregnancy and whelping rate compared with cabergoline. 14 Those authors reported that the whelping rate for early or mid-anoestrus bitches (at 80-160 days after the onset of proestrus) was 12.5% and the rate for late anoestrus bitches (at 200-590 days) was 65.2%.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the litters was similar to that in our previous studies of Beagle breeding using the Ovulation Timing and Ovarian Assessment Test Kit. 15 It may be that deslorelin leads to a poor pregnancy and whelping rate compared with cabergoline. 14 Those authors reported that the whelping rate for early or mid-anoestrus bitches (at 80-160 days after the onset of proestrus) was 12.5% and the rate for late anoestrus bitches (at 200-590 days) was 65.2%.…”
Section: Discussionmentioning
confidence: 99%
“…GnRH agonists have been used for years to control uterine bleeding, to starve endometriotic implants of estrogen stimulation, and to shrink uterine volume in uteri with leiomyoma. GnRH agonists have been utilized as contraceptives in a wide array of different animal species for both female and male animals [6][7][8][9][10][11][12][13][14][15][16]. More recently, an attempt was made to utilize GnRH agonists delivered through an ethylene vinyl-acetate (EVA) vaginal ring in combination with physiologic doses of sex steroids added back for contraception [NCT 00706784].…”
Section: Introduction To the Class Of Compoundsmentioning
confidence: 99%
“…In two studies, deslorelin was effective up to 27 months Sung et al 2006). In another study, still under investigation (Maenhoudt et al 2012), adult bitches treated only once with a 4.7 mg deslorelin implant returned to cyclicity 10.2 AE 5.1 months (2.1-23.3 months) after implantation. The stage of the cycle has no impact on the duration of oestrous suppression after implantation .…”
Section: Gonadotropin Hormone Releasing Agonists and Antagonistsmentioning
confidence: 96%
“…Good fertility rates post‐implantation are to be expected according to Maenhoudt et al. (). In a small trial, all the bitches were pregnant after breeding and the ones allowed to term were able to give birth naturally, with no sign of hypoluteoidism during pregnancy.…”
Section: Gonadotropin Hormone Releasing Agonists and Antagonistsmentioning
confidence: 99%